Natural Convection in Closed-Sided Inclined Channels - Ahmed Habeb (African Journal of Advanced Pure and Applied Sciences, 2025)
Airflow characteristics due to natural convection heat transfer along an inclined channel have been experimentally studied in the current work. The main object of the study was to investigate the airflow and heat transfer under the variations of uniform of heat flux, aspect ratio and the inclination angle. Four values of heat inputs (5 W, 10 W, 15 W, and 20 W), three different aspect ratios (0.45, 0.55 and 0.65) and three various inclination angles (30°, 45°, and 60°) were all tested on channel measured 0.1m by 0.1m. Extensive analysis was performed resulting to practical outcomes. It was found that mass flow rate increases as the heat input and channel depth (or aspect ratio) increase, but decreases as the inclination angle increases. In addition, the average heat-transfer coefficient increases as the heat input increases, but decreases as the channel depth (or aspect ratio) and inclination angle increase. Dimensionless correlations of two and three independent variables were derived for the Nusselt and Reynolds numbers as a function of modified Rayleigh numbers, aspect ratios and inclination angles.